MOTIVATIONAL STRATEGY AND ENGLISH LEARNING ACHIEVEMENT - Fatmawati, Sri; Supardi, Iwan; Fergina, Ana (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstract: The research aimed at finding the correlation between motivational strategy teacher used and students’ English learning achievement. This research applied correlation method as research design. The sample of this research is seventh grade student of SMPN 7 Pontianak in academic year 2016/2017. The data were obtained from Questionnaire and Students’ English Rapor Score.The two data sets are in form of statistics and tabulation which later be calculated in Pearson concept in determining the correlation. The result is 0,747 indicates that a high correlation between two variables of motivational strategies and students achievement. The contribution values both motivational strategy teacher used toward students learning achievement is 55,80 % (r2) which meant that the motivational strategy teacher used give contribution about 55,80 % and the balance 44.20 % is influenced by others variables. The result has been verified by SPPS 17.0 tool. Keywords : Motivational Strategy, Students Achievement, Correlation Abstract:Penelitian ini bertujuan untuk mengetahui hubungan antara strategi motivasi yang digunakan guru terhadap pencapaian siswa dalam belajar bahasa Inggris. Penelitian ini menerapkan metode kolerasi sebagai rancangan penelitian. Subjek penilitian ini adalah siswa kelas 7 dari SMPN 7 Pontianak tahun ajaran 2016/2017. Data data diperoleh dari kuesioner dan nilai rapot bahasa Inggris siswa. Dua data tersebut ditampilkan dalam bentuk statistik dan yang kemudian akan dihitung dengan menggunakan konsep Pearson untuk menentukan korelasi tersebut. Hasilnya adalah 0,747 menunjukkan bahwa adanya korelasi yang tinggi diantara dua variabel tersebut yaitu strategi motivasi yang digunakan guru dan pencapain siswa dalam belajar bahasa Inggris dan kontribusi atau pengaruh strategi yang digunakan guru terhadap hasil pencapaian siswa sebesar 55,80 % dan sebanyak 44.20 % berasal faktor lainya. Hasil tersebut telah diverifikasi dengan menggunakan SPPS 17.0. Keywords: Stragtegi Motivasi, Pencapaian siswa, Hubungan